The Effectiveness of Implementing a Hybrid Work System on the Performance and Motivation of Generation Z Employees in the Digital Era - Indri Febrianti Karunia; Putria Handayani (International Journal Administration, Business & Organization, 2026)
This study aims to analyze the effectiveness of implementing a hybrid work system on the performance and motivation of Generation Z employees in the digital era. The research focuses on how work flexibility, technological support, and leadership style influence the work experience, productivity, and motivation of a generation that values autonomy, freedom, and work-life balance. Utilizing a qualitative approach through in-depth interviews with eight Generation Z employees, the findings indicate that the hybrid work system is perceived as sufficiently effective in supporting workflow and enhancing motivation.Flexibility in work time and location is noted to help improve comfort and boost morale, while technological support and leadership assistance are crucial factors in maintaining performance. This study affirms that the hybrid work model is a relevant and sustainable approach for optimizing the potential of Generation Z and enhancing organizational competitiveness in the digital era.